Feeding adult of Artemia salina (Crustacea-Branchiopoda) on the dinoflagellate Gyrodinium corsicum (Gymnodiniales) and the Chryptophyta Rhodomonas baltica - Costa,Rauquírio André Albuquerque Marinho da (2005)
Experiments were carried out on feeding performance and survival rates of adult Artemia salina exposed to no axenic strains of the dinoflagellate Gyrodinium corsicum and of the Chryptophyta Rhodomonas baltica. Filtration rates on R. baltica and G. corsicum varied from 3.35 to 7.14 ml.artemia-1.h-1 and from 2.97 to 15.86 ml.artemia-1.h-1, respectively. The ingestion rates observed for A. salina did not indicate any digestive dysfunction or physiological impairment for organisms fed on G. corsicum and their functional response were similar to those observed for other organisms like copepod fed on different food concentrations. Mortality rates oscillated from 2.5% to 100% when A. salina was fed on R. baltica or G. corsicum, respectively. Highest mortality rates observed for organisms fed on G. corsicum indicated that this dinoflagellate presented a hazard effect on A. salina that was not possible to confirm if it was related to toxin production or to nutritive inadequacy of this dinoflagellate as food for organisms of this species.